Pengaruh Product Quality, Brand Image, dan Perceived Value terhadap Customer Satisfaction untuk Meningkatkan Repurchase Intention - Dicky Aldian; Muhammad Arief (Jurnal Ekonomi Manajemen Akuntansi, 2025)
Rapid technological advancements have encouraged smartphone sellers to emphasize good product quality to meet customer needs in order to achieve customer satisfaction and repurchase intentions. A positive brand image and good perceived value are important factors in building customer satisfaction, which ultimately impacts repurchase intentions. This study aims to examine the influence of product quality, brand image, and perceived value on customer satisfaction and thus increasing repurchase intentions. The study was conducted in Jakarta with a descriptive causality design through a quantitative approach and purposive sampling technique. Data were obtained from 131 respondents who have used an iPhone. The conceptual model analysis was conducted using the Structural Equation Modeling method. The results show that product quality, brand image, and perceived value significantly increase customer satisfaction. Furthermore, customer satisfaction has been shown to encourage repurchase intentions. In addition, product quality, brand image, and perceived value each have a positive influence on repurchase intentions through the mediation of customer satisfaction. Thus, all hypotheses of this study are proven to have a positive influence. The contribution of this research is expected to provide understanding for producers in developing their business, as well as being a reference for developing marketing strategies that emphasize improving product quality, building a strong brand image, managing value perceptions, and increasing customer satisfaction in order to attract consumer interest in repeating the same product.